Bonding to densely sintered alumina- and glass infiltrated aluminum / zirconium-based ceramics - Valandro, Luiz Felipe [UNESP] (2005)
The objective of this study was to test two hypotheses: (1) silica coating affects the bond strength between ceramics and a resin cement; (2) bond strength is affected by the type of ceramic. Twelve blocks 5 x 6 x 8 mm of In-Ceram Zirconia (ZR) and twelve Procera AllCeram (PR) ceramics were made and duplicated in composite. Five blocks of each ceramic were treated as follows: (1) ZR + GB (laboratorial airborne particles abrasion with Al2O3 particles) + silane; (2) ZR + SC (chairside tribochemical silica coating system, Cojet); (3) PR + GB; (4) PR + SC. Two treated samples of ceramic were analyzed under SEM. The ceramic-composite blocks were cemented with Panavia F and stored in 37ºC distilled water for 7 days. They were then cut to produce bar specimens (n=30) with a bonding area of 0.6±0.1mm². Specimens were loaded to failure under tension in a universal testing machine (1 mm/min). Bond strength (sigma) values were statistically analyzed using ANOVA (Two-way) and Tukey (alpha = 0.05). Mean sigma (MPa) and standard deviation were as follows: 1) 15.1 ± 5.3; 2) 26.8 ± 7.4; 3) 12.7 ± 2.6; 4) 18.5 ± 4.7. Silica coated surfaces showed statistically higher sigma than the same substrate treated with GB only. In addition, ZR (with vitreous phase) showed higher ó than PR (without vitreous phase).